Teknologi Digital dan Kecerdasan Emosional Terhadap Kemampuan Komunikasi Asertif Pada Pemimpin Milenial di PT.GemaSehat Indonesia - Kamil, Ermila (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study aims to analyze the influence of digital technology and emotional intelligence on assertive communication among millennial leaders at PT Gema Sehat Indonesia. The research employed a quantitative approach with an explanatory method. The theoretical foundations of this study are the Technology Acceptance Model (TAM) by Davis, the theory of emotional intelligence by Goleman, and the theory of assertive communication by Alberti and Emmons. The sample was determined using a total sampling technique, with a total of 150 respondents. The research instrument was a questionnaire.The analysis results show that digital technology has a significant effect on assertive communication (p = 0.001 < 0.05). Emotional intelligence also significantly influences assertive communication (p = 0.001 < 0.05). Simultaneously, digital technology and emotional intelligence have a significant impact on assertive communication (F_calculated = 91.533 > F_table = 2.147). The coefficient of determination is 55.5%, indicating that both independent variables have a strong influence, while the remaining 44.5% is influenced by other variables such as leadership style, organizational culture, or digital literacy. This study contributes to the research on millennial leadership and strategic communication planning within organizations.